Towards a Region-Specific Impact Assessment of Water Degradation In Water Footprinting - Natalia Finogenova; Markus Berger; Lennart Schelter; Rike Becker; Tim aus der Beek; Muhammad Usman; Frank-Andreas Weber; Matthias Finkbeiner (Indonesian Journal of Life Cycle Assessment and Sustainability, 2018)
Water footprint evaluates impacts associated with the water use along a product’s life cycle. In order to quantify impacts resulting from water pollution in a comprehensive manner, impact categories, such as human toxicity, were developed in the context of Life Cycle Assessment (LCA). Nevertheless, methods addressing human health impacts often have a low spatial resolution and, thus, are not able to model impacts on a local scale. To address this issue, we develop a region-specific model for the human toxicity impacts for the cotton-textile industry in Punjab, Pakistan. We analysed local cause-effect chains and created a region “Punjab” in the USEtox model using local climate, landscape, and population data. Finally, we calculated human health impacts for the emissions of pesticides from the cotton cultivation and heavy metals from the textile production. The results were compared to that obtained for the region India+ (where Pakistan belongs) provided by USEtox. The overall result obtained for Punjab is higher than that for India+. In Punjab, the dominant pathway is ingestion via drinking water, which contributes to two-thirds of the total impacts. Nevertheless, the USEtox model does not reflect the local cause-effect chains completely due to absence of the groundwater compartment. Since groundwater is the main source for drinking in Punjab, a more detailed analysis of the fate of and exposure to the pollutants is needed. This study demonstrates that a region-specific assessment of the water quality aspects is essential to provide a more robust evaluation of the human health impacts within water footprinting.